BARRIERS TO UTILISATION OF PHYSIOTHERAPY SERVICES AMONG THE ELDERLY IN THE LIVINGSTONE DISTRICT, ZAMBIA - Malambo, Passmore; Marais, Margaret (Journal of Community and Health Sciences, 2020)
Aim: The purpose of this study was to identify the barriers to utilisation of physiotherapy services among elderly people in Zambia. Methods: By means of a convenience sampling technique, 200 elderly people, both males and females aged 60 years and above, were recruited from the Livingstone District in Zambia. A structured questionnaire, developed from literature, was used for collecting data. The Excel software programme and Statistical Package for Social Science (SPSS) were used for the capturing and analyses of the data, using descriptive and inferential statistical analyses. Results: The factors that influenced the utilization of physiotherapy services by the participants were: non-referral to the service, long distances, transport, unavailability of the service in the communities and lack of awareness of physiotherapy. Income was significantly associated (p<0.05) with their inability to go for physiotherapy services. Discussion: The results of this study show that physiotherapy services are not meeting the needs of the elderly in the Livingstone District in Zambia there is a need for the physiotherapy profession to raise awareness of their role in the elderly and become promoters of healthy and active aging by providing services at primary health care level through outreach programmes. Conclusion: Well-coordinated health services that integrate social, economical and physical services for the elderly in the district are recommended in order to achieve active and healthy ageing.